PERBEDAAN SKOR INDEKS PLAK SEBELUM DAN SESUDAH DILAKUKAN PENYULUHAN DENGAN MEDIA VIDEO DAN MODEL STUDI Tinjauan Pada Siswa Tunarungu di SMPLB dan SMALB B Dharma Wanita Banjarmasin - Riznika, Riznika; Adhani, Rosihan; Widya Oktiani, Beta; Hatta, Isnur (FKG Unlam, 2017)
ABSTRACTBackground: The severity of oral health problem of hearing-impaired people is worse than normal-hearing population (tooth caries prevalence 83,92%). Hearing-impaired people have more untreated dental problems. One of the dental problems is plaque. Plaque can be prevented by brushing teeth correctly, which can be taught through socialization. Purpose: This research was aimed to find out the different plaque index scores before and after the socialization through using video and study model to hearing-impaired students at SMPLB and SMALB B Dharma Wanita Banjarmasin. Methods: This research was the quasi experimental, which used pre and posttest with control group design. The research subjects were 24 hearing-impaired students: 12 SMPLB students and 12 SMALB B students. All the subjects had plaques index scores pre-examination and pre-scoring through OâLeary method. Experimental group was socialized through video and study model, and was instructed to brush teeth two times a day for seven days: after having breakfast and before sleeping, whereas control group was not socialized and instructed. After the seventh day, all the subjects had their plaque index score re-examined and re-scored. Results: Showed decrease on experimental groupâs mean score (the first mean 41,35Â±18,76, the final mean 20,37Â±8,36), the paired t-test result was significant(p)=0,001 which showed significant difference. The final mean score of experimental group (20,37Â±8,36) was different from the control groupâs mean score (60,91Â±24,66), the independent t-test was p=0,000, which showed significant difference. Conclusion: There was different plaque index scores before and after the socialization, and also between the experimental and control group.Keywords: plaque, hearing-impaired person, socialization, video, study model